Genetically predicted metabolites mediate the association between lipidome and malignant melanoma of skin - Wu, Yuzhou; Ma, Hang (Frontiers in Oncology, 2024)
ObjectiveTo investigate the causal relationship between lipidome and malignant melanoma of skin (MMOS), while identifying and quantifying the role of metabolites as potential mediators.MethodsA two-sample Mendelian randomization (MR) analysis of lipid species (n=7174) and MMOS was performed using pooled data from genome-wide association studies (GWAS). In addition, we quantified the proportion of metabolite-mediated lipidome effects on MMOS by two-step MR.ResultsThis study identified potential causal relationships between 11 lipids and MMOS, and 40 metabolites and MMOS, respectively. Phosphatidylethanolamine (18:0_18:2) levels mined from 179 lipids by MR Analysis increased the risk of MMOS (OR: 1.962; 95%CI:1.298,2.964; P=0.001). There is no strong evidence for a relationship between genetically predicted MMOS and phosphatidylethanolamine (18:0_18:2) levels (P=0.628). The proportion of gene predictions for phosphatidylethanolamine (18:0_18:2) levels mediated by 1-stearoyl-(glycosylphosphatidylinositol) GPI (18:0) levels was 12.40%.ConclusionThis study identifies 1-stearoyl-GPI (18:0) levels as a potential mediator that may mediate the causal relationship between phosphatidylethanolamine (18:0_18:2) levels and MMOS, This provides direction for the investigation of MMOS, but further research of other possible potential mediators is still needed.